2019
DOI: 10.3389/fcell.2019.00136
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Reprogramming and Emerging Epigenetic Therapies in CML

Abstract: Chronic myeloid leukemia (CML) is a hematopoietic stem cell disorder characterized by BCR-ABL1, an oncogenic fusion gene arising from the Philadelphia chromosome. The development of tyrosine kinase inhibitors (TKIs) to overcome the constitutive tyrosine kinase activity of the BCR-ABL protein has dramatically improved disease management and patient outcomes over the past 20 years. However, the majority of patients are not cured and developing novel therapeutic strategies that target epigenetic processes are a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 179 publications
0
12
0
2
Order By: Relevance
“…Studies illustrated that BCR/ABL‐mediated alteration in histone and non‐histone proteins acetylation has a prominent effect in reprogramming epigenetic mechanisms in favor of cancer cells, resulting in both development and progression of CML (Bugler et al, 2019). Accordingly, it was reasonable to hypothesize that the simultaneous inhibition of HDACs and BCR/ABL could produce superior cytotoxicity in K562 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Studies illustrated that BCR/ABL‐mediated alteration in histone and non‐histone proteins acetylation has a prominent effect in reprogramming epigenetic mechanisms in favor of cancer cells, resulting in both development and progression of CML (Bugler et al, 2019). Accordingly, it was reasonable to hypothesize that the simultaneous inhibition of HDACs and BCR/ABL could produce superior cytotoxicity in K562 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In hematological malignancies, the role of EZH2 may be either oncogenic or tumor suppressive [ 102 , 103 ]. The over-expression of mutant EZH2 has been reported in a wide variety of B-and T-cell lymphoproliferative disorders [ 103 , 104 , 105 , 106 ].…”
Section: Alterations In Inducers Of Methylation Of H3k27 In Cancermentioning
confidence: 99%
“…While the reason for these conflicting results remains to be determined, some evidence shows that in adult HSCs, EZH1 can compensate for EZH2 loss, which can help to explain these discrepancies [ 108 ]. Although many studies use cell lines, primary cells and mouse models of CML have shown dysregulated expression, but no mutations in the PRC2 components [ 102 ]. In MDS and MDS-derived acute myeloid leukemia (AML), EZH2 over-expression is correlated with poor prognosis.…”
Section: Alterations In Inducers Of Methylation Of H3k27 In Cancermentioning
confidence: 99%
“…La farmacocinética de los agentes quimioterapéuticos, es decir, su distribución en el organismo, mecanismo de acción o activación, así como la presencia de barreras fisiológicas como la infiltración del sistema nervioso central por células tumorales, pueden limitar la biodisponibilidad de los fármacos en el sitio activo del proceso tumoral. Este tipo de resistencia, conocido como resistencia farmacológica, puede ser modulada al ajustar la vía de administración, dosis o el esquema de administración del fármaco [11][12][13][14] .…”
Section: Quimioresistencia Tumoralunclassified